Holding Power of Orthopaedic Screws in Femora of Young Calves - Kirpensteijn, J.; Roush, J. K.; St-Jean, G.; DeBowes, R. M.; Gaughan, E. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The holding power and holding power per mm bone width of 4.5 mm and 5.5 mm cortical and 6.5 mm cancellous orthopaedic screws were obtained by load-to-failure studies in excised femora of young female Holstein calves. Mean ( ± SD) holding power (HP), holding power per mm bone width (HPBW), and holding power per cortical bone width (HPCW) of 4.5 mm (179.67 ± 59.74 kg), 5.5 mm (171.46 ± 76.52 kg), and 6.5 mm orthopaedic screws (191.10 ± 56.67 kg) were not significantly different. The HP, HPBW, HPCW, bone width (BW), and cortical width (CW) were not different between left and right femora. The greatest HP was obtained in the proximal femoral diaphysis, while the smallest HP was observed in the proximal and distal metaphysis. The increase in HP was related to the increase in CW, but was not related to the BW. The CW at the insertion sites of orthopaedic screws in femora was significantly less than in metacarpi and metatarsi. The limiting factor of holding power in all tests was the shear strength of the bone.This study compares the holding power, holding power per mm bone width, and holding power per mm cortical width of 4.5 mm and 5.5 mm cortical and 6.5 mm cancellous orthopaedic screws in excised femora of young female Holstein calves. The holding power, holding power per mm bone width, and holding power per mm cortical width of different screws were not significantly different.
Keywords: Holding power; orthopaedic screw; calf; femur